IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN SENI TARI PADA KURIKULUM MERDEKA DI KELAS X SMA NEGERI 1 TUMIJAJAR - Ayu Lestari, Bunga; Habsary, Dwiyana; Kurnia Adzan, Nabilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the deep learning approach in cultural arts learning, particularly dance material, within the Merdeka Curriculum for Grade X students at SMA Negeri 1 Tumijajar. This research employed a descriptive qualitative method. Primary data sources consisted of the cultural arts teacher and students of class X.1, while secondary data included learning materials, lesson plans (RPM), attendance records, students’ score lists, and documentation of learning activities. Data were collected through observation, interviews, and documentation. Data validity was ensured through technique triangulation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of dance learning integrates three principles of deep learning, namely mindful learning, meaningful learning, and joyful learning. The application of mindful learning is reflected in students’ engagement and concentration during the learning process, as well as their ability to reflect on the feedback provided by the teacher. The principle of meaningful learning is demonstrated through students’ ability to understand dance concepts and connect them with practical movement performance in a continuous manner. Meanwhile, joyful learning is manifested through the use of varied instructional media and the provision of teacher appreciation, creating a conducive learning atmosphere that enhances students’ self-confidence and encourages active participation. Despite challenges such as limited instructional time and differences in students’ movement abilities, the deep learning approach is considered effective in supporting dance learning and is aligned with the characteristics and principles of the Merdeka Curriculum.